2015
DOI: 10.1016/j.ypmed.2015.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and changes over time of ideal cardiovascular health metrics among African–Americans: The Jackson Heart Study

Abstract: Objectives To assess the prevalence and changes over time of ideal Life’s Simple Seven (LSS) in African-Americans. Methods Prospective cohort of 5301 African-Americans from the Jackson Heart Study (JHS) from 2000 to 2013. Each of the LSS metrics was categorized as poor, intermediate, or ideal. Results Among men, the prevalence of having 0, 1, 2, 3, 4, 5, 6, and 7 ideal LSS was 3.3%, 23.0%, 33.5%, 24.7%, 11.6%, 3.6%, 0.3%, and 0%, respectively. Corresponding values for women were 1.7%, 26.3%, 33.1%, 22.8%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
66
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 33 publications
7
66
0
2
Order By: Relevance
“…This is comparable with a number of studies from the USA,26 China27 and Korea28 reporting less than 1% of study participants had ideal cardiovascular health. A community-based study of 1933 individuals from USA revealed that only one participant (0.1%) met all ideal cardiovascular health metrics and less than 10% of the participants met five metrics in all subgroups 29.…”
Section: Discussionsupporting
confidence: 85%
“…This is comparable with a number of studies from the USA,26 China27 and Korea28 reporting less than 1% of study participants had ideal cardiovascular health. A community-based study of 1933 individuals from USA revealed that only one participant (0.1%) met all ideal cardiovascular health metrics and less than 10% of the participants met five metrics in all subgroups 29.…”
Section: Discussionsupporting
confidence: 85%
“…We constructed the Simple 7 score for each JHS participant by assigning a score of “1” (ideal status) or “0” (non-ideal) for each of the Simple 7 metrics (Supplemental Table 1) as previously published 4, 10 . For consistency with prior reports 4 , we used metrics already adjudicated within the Jackson Heart Study (as opposed to ideal, intermediate, and poor categories as defined in other work 4 ).…”
Section: Methodsmentioning
confidence: 99%
“…A prime contributor to this racial disparity is a higher prevalence and earlier onset of cardiometabolic disease, including obesity, hypertension, diabetes, and physical inactivity 3 . Though professional guidelines reinforcing ideal cardiovascular health target improvements in cardiometabolic health to prevent disease (“Life’s Simple 7”), recent data in over 5,000 African-Americans from the Jackson Heart Study (JHS) indicate a low prevalence of ideal cardiovascular health characteristics (specifically diet, body mass index, and physical activity) with only modest improvements over time 4 . In largely non-African American populations, achievement of fewer Life’s Simple 7 components is associated with more adverse left ventricular (LV) remodeling 5 and greater cardiovascular and non-cardiovascular disease (CVD) mortality 6, 7 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Fewer Americans, particularly blacks, achieve ideal CVH, especially for BMI, physical activity, and healthy diet, which have been strongly associated with incident diabetes mellitus 7, 8, 9. The association between AHA‐defined ideal CVH and the development of diabetes mellitus is less clear among blacks than among other race‐ethnic groups.…”
Section: Introductionmentioning
confidence: 99%